2016
DOI: 10.5607/en.2016.25.1.33
|View full text |Cite
|
Sign up to set email alerts
|

DrosophilaHomolog of Human KIF22 at the Autism-Linked 16p11.2 Loci Influences Synaptic Connectivity at Larval Neuromuscular Junctions

Abstract: Copy number variations at multiple chromosomal loci, including 16p11.2, have recently been implicated in the pathogenesis of autism spectrum disorder (ASD), a neurodevelopmental disease that affects 1~3% of children worldwide. The aim of this study was to investigate the roles of human genes at the 16p11.2 loci in synaptic development using Drosophila larval neuromuscular junctions (NMJ), a well-established model synapse with stereotypic innervation patterns. We conducted a preliminary genetic screen based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 41 publications
0
29
0
1
Order By: Relevance
“…Choline acetyltransferase, Acetylcholinesterase and Rab4 in Drosophila sensory neurons [ 51 , 52 , 64 66 ]. However, they do not directly affect synaptic bouton formation in the NMJs [ 67 ], compelling us to study the direct impact and correlation of the synapse homeostasis in the CNS neuropil.…”
Section: Discussionmentioning
confidence: 99%
“…Choline acetyltransferase, Acetylcholinesterase and Rab4 in Drosophila sensory neurons [ 51 , 52 , 64 66 ]. However, they do not directly affect synaptic bouton formation in the NMJs [ 67 ], compelling us to study the direct impact and correlation of the synapse homeostasis in the CNS neuropil.…”
Section: Discussionmentioning
confidence: 99%
“…KCTD13 encodes a ubiquitin ligase adaptor ( 114 ) that is reported to have reciprocal effects on zebrafish head size with gain- and loss-of-function ( 35 ). KIF22 is a kinesin-like protein that links chromosomes to the mitotic spindle ( 115 , 116 ), and is necessary for proper embryonic chromosome segregation ( 118 ) and synaptic development ( 34 ). SEZ6L2 is a seizure-related protein that modulates neurite outgrowth ( 117 ).…”
Section: Discussionmentioning
confidence: 99%
“…After complete loss-of-function (LOF) in single genes using antisense techniques, we previously found that 22 of 25 homologs were active during early zebrafish development, but only two ( aldoaa and kif22 ) showed haploinsufficient effects on early brain morphology ( 33 ). A small 16p11.2 screen in Drosophila found that a homolog for KIF22 mediated axonal branching patterns ( 34 ). A single study has reported that suppressing and overexpressing kctd13 has reciprocal effects on head size in zebrafish, and the suggestion was made that this reflected the opposing effects of 16p11.2 CNV deletion and duplication on people ( 35 ).…”
Section: Introductionmentioning
confidence: 99%
“…Second , several recent studies using animal and cellular models have demonstrated the critical involvement of several genes within CNVs towards neurological, cellular and developmental functions (36,37,46,47,51,52) ( Figure 2B ). For example, Blaker-Lee et al .…”
Section: A Case For a Multi-genic Model Of Cnv Pathogenicitymentioning
confidence: 96%